Groin pain caused by iliopsoas synovial cyst treated with endoscopic approach. A case report - Di Benedetto, Paolo; Magnanelli, Stefano; Buttironi, Michele Mario; Beltrame, Alessandro; Causero, Araldo (Acta Biomedica Atenei Parmensis, 2019)
The diagnosis of iliopsoas synovial cyst is a rare finding. The normal approach to treat this condition has been conservative therapies or open surgery, with its associated complications and morbidity. The arthroscopic – endoscopic surgery is less invasive and with an increase in complications and days of hospitalization. We report the case of a 70-year old woman with clinical and imaging signs of a fluid-filled cyst near iliopsoas distal tendon. After fluid aspiration, the patient reported symptom-free interval of several weeks, but then groin pain and swelling feeling return, increased with hip movements. The cyst was removed through arthroscopy approach and the iliopsoas tendon was released. The removal of iliopsoas synovial cyst is necessary to avoid complications such as pain and functional limits. Arthroscopy has the advantage of less soft-tissue damage and quicker recovery. The treatment of associated tendon pathology can be done. Hip arthroscopy can be a safe and effective technique for the removal of iliopsoas synovial cyst.